Hubungan Pengetahuan Ibu dengan Pemberian Imunisasi Dasar dada Bayi di PMB Rini Kecamatan Sunggal Tahun 2023 - Siti Nurmayasari; Basaria Manurung (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
One of the efforts in children's health services to prevent disease is the basic immunization program. Determining the type of immunization is based on expert studies and epidemiological analysis of diseases that arise. This research aims to determine the relationship between maternal knowledge and the provision of basic immunizations in PMB Rini, Sunggal District in 2023. This type of research is research using an analytical survey with a cross sectional method approach. . The population is all mothers who have 1 year old babies registered in PMB Rini, Sunggal District, totaling 42 people. The number of samples used was 42 people obtained using the total sampling technique. The data analysis technique uses chi square. The results obtained in this study were that from 42 respondents, there was a relationship between the maternal knowledge variable and the provision of basic immunization with a value of p = 0.023. It is recommended that the community health center increase the knowledge of mothers who have 1 year old babies to increase education regarding the provision of basic immunization.